Triodia laetus (Staudinger, 1877) – new species of ghost moths (Lepidoptera, Hepialidae) for the fauna of Russia, Armenia and Azerbaijan - Svyatoslav A. Knyazev (Acta Biologica Sibirica)
A poorly-known Hepialidae species Triodia laetus (Staudinger, 1877) is reported from the territory of Russia, Armenia, and Azerbaijan for the first time. The new locations proved its wide distribution in the Caucasus and Transcaucasia. Type specimens, materials from museum and private collections, as well as photographic observations on iNaturalist were studied. A description of the external characteristics of the male and female is given, as well as a description and images of the genitals. The distinctive features are compared with the closely related species Triodia sylvina (Linnaeus, 1761).